Adição de ensinos da matemática ao jogo educativo “as aventuras de amaru” - FARIAS, Abner Gillet (2019)
This work aims to expand the project "The Adventures of Amaru", to complement the teaching of basic mathematical concepts, such as addition and subtraction, through the insertion of games to make the learning experience fun. The discipline of math is considered by many to be tedious and difficult to learn, and this view mainly reflects on children and adolescents. This lack of interest in the numbers ends up putting underdeveloped countries such as Brazil in terrible positions in the world rankings of education. One of the main factors for these results is the way it is taught where many teachers simply put their students to do abstract calculations with no real-life context or some form of play element to maintain their attention and learning. However, there are new methodologies that seek to change this reality, and one of them is gamification, which seeks to integrate elements of playful games into scenarios where they do not normally fit. This technique proves to be quite efficient, and the project "The Adventures of Amaru" is a fruit of this technique. With a simple narrative and using an educational structure made by psychologists, this game complements the Portuguese language classes of the first year of elementary school. Due to its positive results, the need to expand this project was felt. After the changes are made, this project can serve as a tool to support the teaching of mathematics in schools, so that it can improve the quality of teaching in Brazil.